Effects of Crack Depth on the Mode Shapes and Natural Frequencies of Y-Junction Pipes - Gardezi, S. A. R.; Mughal, H. U.; Rehman, A. U.; Bari, A.; Zaman, M. F. (The Nucleus, 2016)
Maintenance shutdowns are not affordable in process industries due to certain economic factors. Piping system in any process plant is key element and therefore must be monitored carefully to detect any damage in its initiation or early propagation stage. This research work aims to establish an effectual understanding of vibration behavior of piping structures in the process industry. Y-junction piping models having 3 cases are crack modelled, mapped mesh and analyzed in Ansys APDLÂ®. Natural frequency data is gathered from the analysis and the data of all three cases is compared to see the effects of the crack angles on the modes and natural frequencies of the models.